2013
DOI: 10.1002/atr.1223
|View full text |Cite
|
Sign up to set email alerts
|

Personal space, evasive movement and pedestrian level of service

Abstract: SUMMARYThis study proposed a behavioral theory-based approach to better assess pedestrian levels of service for sidewalks, using the concepts of personal space and pedestrian evasive movements. Data from pedestrian interviews and video recordings at 28 commercial, residential, and leisure locations were used to analyze the effects of pedestrian movements on pedestrian perceived levels of service. With these results, a new measure of pedestrian level of service was developed. With the use of a separate validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 27 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…Pedestrian has to deviate laterally to avoid sidewalk vendor and its customer while maintaining a personal space from opposing pedestrians. The implication of this finding could be a decline in pedestrian perceived PLOS with presence of sidewalk vendor because pedestrian perceived PLOS decline in with an increase in number of evasive actions by a pedestrian [13]. The result also supports previous recommendations to leave a continuous clear pedestrian path while allocating a vending stall [28].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Pedestrian has to deviate laterally to avoid sidewalk vendor and its customer while maintaining a personal space from opposing pedestrians. The implication of this finding could be a decline in pedestrian perceived PLOS with presence of sidewalk vendor because pedestrian perceived PLOS decline in with an increase in number of evasive actions by a pedestrian [13]. The result also supports previous recommendations to leave a continuous clear pedestrian path while allocating a vending stall [28].…”
Section: Discussionsupporting
confidence: 81%
“…A study in Lima, Peru, used a multivariate model and showed that the number of sidewalk vendors is significantly correlated with pedestrian road crossing crash risk [9]. A study conducted Seoul, Korea used a multiple regression technique to identify contribution of number of pedestrians evasive actions from a video observation to perceived PLOS from field interview [13]. The study defined five categories of evasive movements that may vary based on pedestrian traffic flow [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, studies regarding Pedestrian Interactive Behaviours (PIBs) including overtaking behaviour [1][2][3][4][5], evasive behaviour [6][7][8] and weaving behaviour [9][10] have been conducted on walkways. Previous studies mainly focused on two aspects of PIBs: (1) distances necessary for taking behaviours to occur (micro level);…”
Section: Introductionmentioning
confidence: 99%